PENGARUH PENGGUNAAN MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR MATERI SENI RUPA PESERTA DIDIK KELAS VII DI SMPN 02 RANAH AMPEK HULU TAPAN - Okta Yunita Putri; Yofita Sandra (Serupa The Journal of Art Education, 2020)
Okta Yunita Putri (2020): The Influence of Using Audio Visual Media on Learning Outcomes of  Class VII Students in Visual Arts at SMPN 02 Ranah Ampek Hulu Tapan. Thesis Department of Fine Arts, FBS UNP. This research was conducted in order to find out the purpose of the effect of the use of audio visual media on the learning outcomes of class VII students in SMPN 02 Ranah Ampek Hulu Tapan. The method used in this research is quasi-experimental (quasi-experimental) and in this study using a Non Equivalent Control Group Design. The sampling design used was purposive sampling. After all tests are carried out, the Sig value can be obtained. (2-tailed as much as (0.003 <0.005) and the post-test tcount of 3.102, greater than ttable (0.3102> 2,000), then H0 is rejected and H1 is accepted, therefore the learning outcomes of the experimental group are significantly different Compared with the control group, the researcher concluded that the use of Audio Visual media had a positive (good) effect and significantly different on the learning outcomes of students in the learning process of visual art material for class VII at SMPN 02 Ranah Ampek Hulu Tapan.Keywords : Media, Audio Visual, Learning Outcomes, Fine Arts